Economic rights and environmental wrongs property rights for the common good - Devlin, Rose Anne, 1956-; Grafton, R. Quentin, 1962-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 1998)
The crisis of environmental degradation has createcharemd an immense volume of literature which focuses on controlling environmental problems. Economic Rights and Environmental Wrongs goes one step further to extend and complement the current debates.
1. Environmental wrongs -- 2. Externalities and the environment -- 3. Property rights for pollution -- 4. Property rights for natural resources -- 5. Controlling environmental degradation without property rights -- 6. Property rights for the common good.
"Paperback edition 1999."
Includes bibliographical references and index.
Keywords: Environmental degradation -- Economic aspects; Environmental economics; Right of property; Environmental responsibility; Electronic books